Tinjauan Pengaruh Zeolit terhadap Laju Korosi Baja Karbon dalam Medium Asam Mineral (H2SO4) dan Minuman Berkarbonasi - Bambang Hari P (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Zeolites are alumino silicate compounds having a three-dimensional structure with tetrahedral arrangement of units (AlO4)-5 and (SiO4)-4. The zeolite cations are located outside the tetra hedral that can move freely in the cavities of the zeolite particles and acts as a counter ion exchange with other cations outside the zeolite. The properties is what underlies of zeolite as cation exchanger. Carbonated beverages are drinks that are given CO2 pressurized and has a low pH. Although carbonated beverages have a low pH, but it not corrosive. Corrosion is an electrochemical reaction that is certainly the case in the metal when in contact with either dry or wet environments. Corrosion is degradation process with the environment so as to reduce the strength of metal. This research was conducted by immersing the test specimen which was given stress and not given stress in medium (H2SO4) and carbonated beverages mediums with the addition of zeolite particles and without the addition of zeolite particles. The desired result is to know the corrosion rate of mild steel in an environment of carbonated beverages and H2SO4 acid solution in the same pH by using the weight loss method, as well as to determine the effect of zeolite particles on the corrosion rate. The survey results revealed that the addition of zeolite particles can inhibit the corrosion rate of the steel that was given stress is 22,11% in the H2SO4 medium, medium A is 17,39%, medium B is 16,63% and raise the pH of H2SO4 by 150%, medium A 88,46% and medium B 92,308%.